1993
DOI: 10.1017/s0965539500000875
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical screening for Down’s syndrome in the first trimester of pregnancy

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0965539500000875How to cite this article: MCM Macintosh and T Chard (1993). Biochemical screening for Down's syndrome in the rst trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Intact hCG, placental alkaline phosphatase, and pregnancyspecrfic pl glycoprotein are weak markers for Down's syndrome in the first trimester (Brock er al., 1990;Aitken et al, 1993) and although UE3 levels have been reported to be reduced in Down's syndrome pregnancies in both the first and the second trimesters (Aitken et aZ., 1993), the available assays are not optimized for routine first-trimester screening. Several studies have shown that PAPP-A levels are sigmfkantly reduced in first-trimester Down's syndrome pregnancies (Brambati et aL, 1993;Macintosh and Chard, 1993;Spencer et al, 1994) but that levels are unchanged in the second trimester . The potential of PAPP-A as a marker is therefore complicated by the apparent normalization in levels in abnormal pregnancies between the first and second trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…Intact hCG, placental alkaline phosphatase, and pregnancyspecrfic pl glycoprotein are weak markers for Down's syndrome in the first trimester (Brock er al., 1990;Aitken et al, 1993) and although UE3 levels have been reported to be reduced in Down's syndrome pregnancies in both the first and the second trimesters (Aitken et aZ., 1993), the available assays are not optimized for routine first-trimester screening. Several studies have shown that PAPP-A levels are sigmfkantly reduced in first-trimester Down's syndrome pregnancies (Brambati et aL, 1993;Macintosh and Chard, 1993;Spencer et al, 1994) but that levels are unchanged in the second trimester . The potential of PAPP-A as a marker is therefore complicated by the apparent normalization in levels in abnormal pregnancies between the first and second trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…AFP, P-hCG, and estriol are commonly used in screening for Down's syndrome [4], However, efforts to enable earlier diagnosis have expanded the search for other possible markers, including PAPP-A, Inhibin, and urinary (3-core hCG [5,6], Estradiol, PAI-2, and many other protein markers have also been theorized to predict pregnancy outcomes. Serum progesterone has been used to discrimi nate between normal and abnormal pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, it would be desirable if sensitive and specific screening could be applied in the first trimester, affording earlier termination of pregnancy if indicated. To this end, a number of fetal and placental proteins have undergone initial evaluation of their usefulness as first-trimester maternal serum markers for Down's syndrome (Macintosh and Chard, 1993). Also, it has been recently reported that immunoreactive inhibin, a glycoprotein of placental origin in pregnancy (Abe et al, 1990;Tovanabutra et al, 1993), did not appear useful in first-trimester screening for Down's syndrome (van Lith et al, 1994;Wallace et al, 1994), although some potential value in the second trimester has been suggested (van Lith et al, 1992;Spencer et al, 1993;Cuckle et al, 1994).…”
Section: Introductionmentioning
confidence: 99%